2018
DOI: 10.22146/gamaijb.27552
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Factors of the Collaborative Consumption in the Era of Sharing Economy

Abstract: The aim of this study was to analyze the motivational factors of collaborative consumption in the era of the sharing economy, as a part of consumers’ behavior by online media platforms. Collaborative consumption is about people’s willingness to share and to collaborate to meet certain needs. The study used the qualitative method with interviews for the data’s collection. The context of the study was using consumers who had experience of using Airbnb, Go-Jek, and selling their product via online media. Twenty-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…The strongest motivations to buy a product made of waste or recycled material were: (1) the effort to help solve perceived global environmental problems (322 respondents, 60%; respondents in generation Y and Z preferred this motivation) and ( 2) the support of a business idea with good intentions (200 respondents, 42%). Mayasari & Haryanto (2018) declare different motives for people to accept new circular offerings -economic benefits, exclusivity of ownership, social bonds and networking, emotional and ecological aspects as well as personal values. A study by Singh et al (2019) in the UK found several perceived benefits of upcycling -economic and environmental profits followed by enjoyment, fun, and feel-good reasons.…”
Section: Resultsmentioning
confidence: 99%
“…The strongest motivations to buy a product made of waste or recycled material were: (1) the effort to help solve perceived global environmental problems (322 respondents, 60%; respondents in generation Y and Z preferred this motivation) and ( 2) the support of a business idea with good intentions (200 respondents, 42%). Mayasari & Haryanto (2018) declare different motives for people to accept new circular offerings -economic benefits, exclusivity of ownership, social bonds and networking, emotional and ecological aspects as well as personal values. A study by Singh et al (2019) in the UK found several perceived benefits of upcycling -economic and environmental profits followed by enjoyment, fun, and feel-good reasons.…”
Section: Resultsmentioning
confidence: 99%
“…Enjoyment, the fourth predictor in the CSBT, is considered one of the emotional aspects of collaborative and sharing behaviors. Consumers are trying to do something different from their daily lives routine, and it is always fun to interact with community members in a meaningful way (Mayasari and Haryanto, 2018). It was proved that enjoyment plays an important role in attitude formation and intention (Hamari et al.…”
Section: Research Propositions For Future Researchmentioning
confidence: 99%
“…Modern urban societies have many advantages due to technological advancements, such as online ridesharing. This new way of commuting offers affordable services, more efficient use of time, and ease of accessibility (Mayasari & Haryanto, 2018). As a result, there is a rapidly growing demand for online ridesharing services in big cities, such as Jakarta, particularly for motorcycle ridesharing services.…”
Section: Work-sense Of Coherence and Driver Stressmentioning
confidence: 99%